1999
DOI: 10.1017/s0963548399003831
|View full text |Cite
|
Sign up to set email alerts
|

On the Structure of Dense Triangle-Free Graphs

Abstract: As a consequence of an early result of Pach we show that every maximal triangle-free graph is either homomorphic with a member of a specific infinite sequence of graphs or contains the Petersen graph minus one vertex as a subgraph. From this result and further structural observations we derive that, if a (not necessarily maximal) triangle-free graph of order n has minimum degree δ[ges ]n/3, then the graph is either homomorphic with a member of the indicated family or contains the Petersen graph with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 16 publications
1
36
0
2
Order By: Relevance
“…Concerning graphs with circular chromatic numbers at least 3, there are some interesting characterizations of such graphs which follow from a recent result of Brandt [3] and an earlier result of Pach [11]. Both Brandt and Pach were aiming at some other problems.…”
Section: Theorem 5 Supposementioning
confidence: 96%
“…Concerning graphs with circular chromatic numbers at least 3, there are some interesting characterizations of such graphs which follow from a recent result of Brandt [3] and an earlier result of Pach [11]. Both Brandt and Pach were aiming at some other problems.…”
Section: Theorem 5 Supposementioning
confidence: 96%
“…The following special class of maximal triangle-free graphs plays an important role in the investigation on dense triangle-free graphs, see [1]. For an integer k ∈ N , the graph F k has V (F k ) = {v 1 , v 2 , .…”
Section: Structure Of Maximal Triangle-free Graphsmentioning
confidence: 99%
“…In 1995, this result was rediscovered by Brouwer [5], who gave a considerably simpler proof. While the original characterization needs some introduction, which will be given later, the second author [4] observed that there are two forbidden subgraph formulations characterizing these graphs. A triangle-free graph has the property that every independent set is contained in the neighborhood of a vertex if and only if it is maximal triangle-free and contains no 6-cycle as an induced subgraph, or, equivalently, no vertex-deleted Petersen graph as a (not necessarily induced) subgraph.…”
mentioning
confidence: 99%
“…A triangle-free graph has the property that every independent set is contained in the neighborhood of a vertex if and only if it is maximal triangle-free and contains no 6-cycle as an induced subgraph, or, equivalently, no vertex-deleted Petersen graph as a (not necessarily induced) subgraph. The forbidden subgraph characterizations turned out to be helpful for the application of Pach's result to problems on triangle-free graphs with large minimum degree [4].…”
mentioning
confidence: 99%